2022
DOI: 10.3390/biology11020255
|View full text |Cite
|
Sign up to set email alerts
|

Procollagen C-Endopeptidase Enhancer 2 Secreted by Tonsil-Derived Mesenchymal Stem Cells Increases the Oxidative Burst of Promyelocytic HL-60 Cells

Abstract: Reactive oxygen species (ROS) generated by neutrophils provide a frontline defence against invading pathogens. We investigated the supportive effect of tonsil-derived mesenchymal stem cells (TMSCs) on ROS generation from neutrophils using promyelocytic HL-60 cells. Methods: Differentiated HL-60 (dHL-60) cells were cocultured with TMSCs isolated from 25 independent donors, and ROS generation in dHL-60 cells was measured using luminescence. RNA sequencing and real-time PCR were performed to identify the candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Furthermore, PCOLCE plays a key role in promoting lung metastasis of osteosarcoma [ 40 ] and participates in EMT [ 41 ]. A recent study has shown that PCOLCE2 stimulates the production of reactive oxygen species in neutrophils [ 42 ]. Moreover, a study has shown a correlation between PCOLCE2 and ferroptosis in colon adenocarcinoma [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PCOLCE plays a key role in promoting lung metastasis of osteosarcoma [ 40 ] and participates in EMT [ 41 ]. A recent study has shown that PCOLCE2 stimulates the production of reactive oxygen species in neutrophils [ 42 ]. Moreover, a study has shown a correlation between PCOLCE2 and ferroptosis in colon adenocarcinoma [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that ACCN2 may affect the development of SHPT. Tonsil-derived mesenchymal stem cells can increase reactive oxygen species (ROS) production of neutrophils through PCOLCE2, thus enhancing host defense ( Yoon et al, 2022 ). Within living cells, mitochondria are considered relevant sources of ROS ( Willems et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…MTT assay was performed as described previously (Yoon et al, 2022). Briefly, primary murine hepatocytes cultured in DMEM supplemented with 0.1% BSA were treated with paracetamol (10 mM) for 24 h. Then, methylthiazolyldiphenyl‐tetrazolium bromide (MTT, Sigma; M5655) solution was added to each well with a final concentration of 0.5 mg·ml−1, and cells were incubated for 4 h. After the medium was carefully removed, DMSO was added to each well and absorbance was measured at 570 nm using a plate reader, Synergy H1M (Molecular Devices, Sunnyvale, CA, USA).…”
Section: Methodsmentioning
confidence: 99%